Георадарный метод обнаружения водонасыщенных слоев грунта с оценкой их объемной влажности - Сугак, В.Г.; Овчинкин, О.А.; Силаев, Ю.С.; Сугак, А.В. (Геофизический журнал, 2014)
Geo-radar method of revealing ground water local zones in upper ground layers (up to 20—30 m) with evaluation of their three-dimensional humidity concerning the sounding signal with stepwise alteration of its carrier frequency has been considered. The method is based on phase structure of reflected signals which characteristics are determined to essential degree by three-dimensional humidity of ground rocks. Effectiveness of the method was evaluated by practical example of revealing water-saturated ground layers at the depths up to 20 m and was confirmed by the data of drilling and laboratory tests. Розглянуто георадарний метод виявлення локальних зон ґрунтових вод у верхніх шарах ґрунту (до 20—30 м) з оцінкою їх об‘ємної вологості стосовно зондувального сигналу з покроковою зміною його несучої частоти. Метод засновано на застосуванні фазової структури відбитих сигналів, характеристики якої значною мірою визначаються об‘ємною вологістю порід ґрунту. Ефективність методу оцінено на практичному прикладі виявлення насичених водою шарів ґрунту на глибинах до 20 м і підтверджено даними буріння та лабораторних випробувань.